Manfaat Interaksi Teman Sebaya Terhadap Perilaku Sosial Anak Usia Dini Di Ra Muslimat Nu 007 Gandu 1 Mlarak Kabupaten Ponorogo Provinsi Jawa Timur - Farida, Nuning; Friani, Devi Anggi (JURNAL SOSIAL : Jurnal Penelitian Ilmu-Ilmu Sosial, 2018)
To create a good social environment for children, peers are needed, because peers have an important role in creating a social environment that supports the development of children's social behavior. In life among peers there is a social process in which processes influence and influence each other. This research is a descriptive qualitative study, data obtained by observation, in-depth interviews, and documentation. The validity of the data technique uses triangulation techniques. Analysis of qualitative data is carried out interactively and takes place continuously until complete, so the data is saturated. Activities in data analysis are data reduction, data display, and conclusion drawing / verification ". From the results of the study, it can be seen that the social behavior of early childhood at Muslimat RA NU 007 Gandu 1 Mlarak Ponorogo develops well which can be proven by the existence of mutual help, mutual respect, mutual cooperation, being able to distinguish between good and bad and being able to be polite. peers are also developing well. The benefits of peer interaction with early childhood social behavior include children can learn to respect others, have an attitude of responsibility, learn to work together, share and care about the conditions of other friends. They learn to empathize and start learning to help friends who are in trouble.